Psychotherapy in recurrent depression: efficacy, pitfalls, and recommendations. (1st November 2020) - Cosci, Fiammetta; Guidi, Jenny; Mansueto, Giovanni; Fava, Giovanni A.
ABSTRACT: Introduction: Most people who seek treatment for depression experience relapse or recurrence, thus prevention represents a very important way to reduce suffering and burdens associated with this illness. Areas covered: Preventive psychological interventions after depression remission include maintenance psychotherapy after an initial course of psychological treatment and the sequential model, i.e. the use of psychotherapy after pharmacotherapy or the application of drug treatment after a course of psychotherapy. Maintenance psychotherapy is aimed to prolong the effects obtained in the previous treatment course. The sequential model appeared to be more effective than monotherapy or the simultaneous combination of two different interventions. Expert opinion: The patient should be informed about the prognosis of depressive illness and treatment options. One option would be to continue with an antidepressant drug indefinitely; however, loss of clinical effect may occur. The other option would be to start working on the prevention of the next episode. Thus, a sequential approach might be proposed. It includes antidepressants in the acute phase and a short-term course of cognitive-behavioral therapy in the residual phase. This approach has been specifically applied for its preventive effects. Completing the psychotherapy course with sessions of Well-Being Therapy would be optimal to enhance psychological well-being and euthymia.